2016
DOI: 10.1002/ajim.22646
|View full text |Cite
|
Sign up to set email alerts
|

Methodological concerns related to response bias in migrant and seasonal farmworkers

Abstract: Unique survey methodologies must be used with MSFWs, who tend to have low research literacy and are particularly susceptible to response bias. Objective study outcomes are particularly favorable in this population in order to minimize dependence on self-reported measures. Am. J. Ind. Med. 59:1112-1119, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Similar to Benson et al (2016), we encountered anecdotal evidence of a response bias in our target population and participants tended to respond favourably. Therefore, we need to use caution when conducting user testing.…”
Section: Discussion On Community-supported Design and Feasibilitymentioning
confidence: 70%
See 2 more Smart Citations
“…Similar to Benson et al (2016), we encountered anecdotal evidence of a response bias in our target population and participants tended to respond favourably. Therefore, we need to use caution when conducting user testing.…”
Section: Discussion On Community-supported Design and Feasibilitymentioning
confidence: 70%
“…This extends to interactions with researchers as well. Hispanics exhibit a bias to ‘yea-saying’ (answering questions in the affirmative) greater than the general US population (Aday, Chiu, and Andersen 1980; Benson et al 2016). Hispanic women may have trouble with survey questionnaires, commonly used to assess user experience.…”
Section: Designing Mhealth Applications For Hispanic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, this study only evaluated the impact of food insecurity quantitatively, whilst ignoring the qualitative impact of food insecurity and child hunger, such as the household’s specific and personal perception, experiences, and coping strategies used to mitigate the effects of food insecurity during the MCO period. Fifth, acquiescence and recall biases are also common in a face-to-face survey, particularly when it is conducted among individuals with low socioeconomic backgrounds [ 77 ]. Moreover, a single dietary record may not actually reflect the children’s usual food intake pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the use of power‐take off (PTO) shields on PTO drivelines, which prevent workers from becoming entangled, the self‐reported use of driveline shields was nearly double that which was identified in on‐farm equipment audits . In another research project conducted with migrant farmworkers in the NY Hudson Valley farming region, researchers found that there was a strong tendency for farmworkers to report favorable evaluations of safety innovations, despite evidence of not adopting the innovation . Other studies have identified varying rates of accuracy in self‐reported PPE use relating to the worker environment …”
Section: Introductionmentioning
confidence: 99%